Seznam slovenskih imen v Sloveniji živečih sovk (Lepidoptera, Noctuidea) - Jež, Matjaž (Acta entomologica slovenica (Ljubljana), 2023)
A checklist of owlet moths (Noctuidae) of Slovenia with Latin and Slovenian binary names is presented, comprising 191 genera and 474 species. The list is based on Hafner’s list of butterflies of Carniola from 1910, supplemented by Carnelutti’s list from 1992. The two lists are updated faunistically and taxonomically with ours own and other publicly available data. The main purpose of this paper is to present the Slovenian names of owlet moths and the method of their derivation. A brief history of the development of species names in Europe and Slovenia is also presented. The Slovenian names were determined according to the principle of Line’s binary nomenclature, taking into account the etymology of the Latin names and a nature of owlet moths.
Keywords: metulji; moths; owlet moths; Slovenia; Slovenija; sovke